The physiological mechanism and effect of resistance exercise on cognitive function in the elderly people - Cheng, Aijie; Zhao, Zhiwei; Liu, Hengxu; Yang, Jinxin; Luo, Jiong (Frontiers in Public Health, 2022)
Background As brain function declines and cognitive ability declines, the benefits of resistance exercise to the brain of older people are gradually gaining attention. Objective The purpose of this review is to explore the mechanism and relationship between physiological factors such as vascular and neuronal degeneration and cognitive decline, and to categorize the differences in the effects of an acute and chronic resistance exercise intervention on cognitive function in healthy elderly people and the possible regulators of cognitive effects. Methods Using PubMed, Elsevier, Web of Science, X-MOL, CNKI, and Taiwan academic literature database, the research papers published in relevant journals at home and abroad until April 2022 were searched with Chinese and English keywords such as Resistance exercise, the elderly, hippocampus, memory performance, neurons, cognitive function. Pedro scale was used to check the quality of various documents, and the relevant research documents were obtained with the resistance exercise elements as the main axis for comprehensive analysis. Results and conclusion (1) Resistance exercise can have a beneficial effect on the brain function of the elderly through blood flow changes, stimulate nerve conduction substances and endocrine metabolism, promote cerebrovascular regeneration and gray matter volume of the brain, and prevent or delay the cognitive function degradation such as memory and attention of the elderly; (2) Acute resistance can temporarily stimulate hormone secretion in vivo and significantly improve the effect of short-term memory test, but it has little effect on the cognitive performance of the elderly; (3) Moderate-high intensity resistance exercise (50–80%1RM, 1–3 times/week, 2–3 groups/time) lasting for at least 6 months is more prominent for the improvement of cognitive function of the elderly, while the parameters such as resistance exercise intensity, exercise amount, duration, evaluation test time and differences of subjects may have different degrees of influence on cognitive benefits.